PENGARUH PEMBERIAN EKSTRAK DAUN PEPAYA (Carica papaya Linn) TERFERMENTASI DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN DAN SINTASAN BENIH IKAN NILA (Oreochromis niloticus) UKURAN 19,2 g PADA BAK PENELITIAN - Astutik, Defy; Wirawan, Indra; Agustini, Maria (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Tilapia (Oreochromis niloticus) is one type of freshwater fish that tends to be strong against disease disorders commonly experienced by other types of freshwater fish and has tolerance to water quality in a wide range. Giving brobiotics with a mixture of natural ingredients is very important in adding nutrients to support tilapia growth. The purpose of this study was to determine the effect of adding a mixture of probiotics and papaya leaf extract to artificial feed (pellets) on the growth and survival of tilapia seeds. Data collection methods using experimental methods. The design used in this study was a completely randomized design (CRD) with 3 treatments and 6 replicates. The treatments were A (25g papaya leaf extract/100g feed), B (50g papaya leaf extract/100g feed) and C (75g papaya leaf extract/100g feed). The results showed that the addition of fermented papaya leaf extract to tilapia feed had a very significant effect on the growth and survival of tilapia fry. Treatment B gave the highest absolute weight growth of 3.42 gr/head with an average weight of 16.88 gr and survival value reached 88%. While in treatment A with a dose of papaya leaf extract of 25 g and C with a dose of extract of 75 g has absolute weight growth that is not significantly different. Where the average value in treatment A is 13.47 gr with 87% survival and C has an average of 13.70 with 83% survival. Water quality data during the study obtained pH ranged (7.8 - 8.1), DO (4.12 - 6.79), Temperature (27.5 - 28.5) and NH4 (0 - 0.35). The results of the analysis of variance (ANOVA) of the four parameters showed no difference between treatments and were in the range of life of tilapia (Oreochromis niloticus).